The interplay of carbon and nitrogen cycling driven by watershed microorganisms - Sun, Guijia; Zou, Qiang; Wang, Bing (Frontiers in Microbiology, 2026)
Microorganisms play central roles in regulating carbon and nitrogen cycling across watersheds, driving processes such as organic matter decomposition, primary production, nitrification, and denitrification. Rapid advances in high-throughput sequencing and environmental monitoring have enabled unprecedented insights into the taxonomic diversity and functional capacities of microbial communities under global change. In this review, we synthesize findings from studies published in recent years to evaluate how hydrological connectivity, redox gradients, temperature shifts, and nutrient loading shape microbial metabolism across rivers, lakes, wetlands, and coastal interfaces. We further summarize emerging evidence on how antibiotic resistance genes (ARGs) propagate through these ecosystems and influence microbial functions. The integration of multi-omics technologies including metagenomics, metatranscriptomics, combined with ecological and biogeochemical modeling provides new opportunities to quantify microbe-mediated carbon sequestration and nitrogen transformation. Finally, we discuss current knowledge gaps, including the limited understanding of ARG-driven community restructuring and the insufficient mechanistic resolution of microbe–environment interactions under future climate scenarios. This review highlights the need for cross-scale, data-integrated frameworks to better predict how microbial processes regulate watershed-level biogeochemical cycles in a rapidly changing world.